Comparing minoxidil-finasteride mixed solution with minoxidil solution alone for male androgenetic alopecia: a systematic review and meta-analysis of randomized controlled trials - Li, Yulong; Huang, Qianqian; Zhou, Zhongbao; Zhang, Yong (Frontiers in Medicine, 2025)
BackgroundThis meta-analysis aimed to evaluate the efficacy of topical minoxidil-finasteride combination (MFX) versus minoxidil monotherapy (MNX) for male androgenetic alopecia (AGA).MethodsFollowing PRISMA 2020 guidelines, we systematically searched PubMed, Embase, and Cochrane Central Register of Controlled Trials from inception through May 2025. Methodological quality was assessed using Cochrane Risk of Bias 2.0 tool, with statistical analyses performed using RevMan 5.3 and evidence certainty evaluated through GRADEpro GDT. CRD420251054497.ResultsThis meta-analysis of seven RCTs (N = 396) demonstrated superior efficacy of topical minoxidil-finasteride combination (MFX) over monotherapy (MNX) for male androgenetic alopecia. Pooled analyses showed clinically meaningful improvements in hair density (MD = 9.22, p = 0.04), hair diameter (MD = 2.26, p = 0.005), and global photographic assessment (MD = 0.79, p < 0.00001), all exceeding minimal clinically important thresholds. The treatment effect followed a hierarchical pattern, with MFX showing strongest benefits for marked improvement (OR = 3.29, p = 0.015) and more variable results for moderate outcomes. While primary outcomes demonstrated robust effects with moderate certainty evidence, observed heterogeneity in some endpoints and sample size limitations suggest the need for standardized assessment methods and larger confirmatory studies to strengthen these conclusions.ConclusionTopical minoxidil-finasteride combination therapy demonstrates superior efficacy over monotherapy for male AGA, supporting its clinical adoption. However, larger, standardized trials are needed to confirm long-term outcomes and optimize treatment protocols.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251054497, identifier CRD420251054497.